TARI GITEK BALEN SEBAGAI REPRESENTASI KESENIAN BETAWI - Maulita Meysanti Setiawan; Ida Bagus Ketut Sudiasa; Sulistiani (Jurnal Pendidikan Tari, 2025)
The Gitek Balen Dance is a Betawi dance created from the development of the Betawi Mask movement. This dance has become a medium of representation of Betawi culture and continues to develop until now, both in movement, musical accompaniment, and costumes. This study explains how the Gitek Balen Dance represents Betawi culture through movement, music, and costumes, as well as how the form of its presentation has evolved since its creation until 2025. Using a descriptive qualitative approach and Ferdinand de Saussure's semiotic theory. Data collected through interviews, observations, and documentation studies of creators, dancers, and three dance studios, the Gitek Balen dance features elements of Betawi culture through a system of signs on movement, gamelan mask music, and distinctive costumes. This dance has three versions of presentation and is now part of the curriculum in one of the studios and art schools. The Gitek Balen dance is a new dance creation that reflects the dynamic soul of young girls. The simplification of movement and the form of the dish shows adaptation to needs, but its essence and existence are maintained until now.